Enhancing second-order empathy in medical practice by supplementing patients’ narratives with certainties - José María Ariso (BMC Medical Education, 2018)
Abstract Most scholars agree that empathy is one of the keys for medical education, but it is not yet clear precisely how this term should be defined. Currently, the predominant tendency in this area consists in considering empathy within the context of narrative medicine or, more specifically, within the interaction theory instead of the simulation theory of empathy. A significant development of the interaction theory is “second-order empathy”. After describing the outlines of this kind of empathy, I suggest that the practitioner should also inquire about the patient’s certainties – in Wittgenstein’s sense – in order the better to enrich and understand her narrative. Besides offering examples of how certainties may contribute to reaching a clearer perspective of the patient’s narratives and, thus, to strengthen second-order empathy with her, guidelines are provided to train medical students in identifying such certainties.